La mujer embarazada como carga familiar en los incidentes de rebaja de pensión alimenticia en el Cantón Guaranda, año 2022. - Sánchez Gavilánez, Karina Isabel (2024)
In Ecuador, the right to food for pregnant women is enshrined in the Code of Children and Adolescents, which establishes that pregnant women have the right to food to meet their needs for food, health, clothing, housing, care during childbirth, the puerperium, and during the breastfeeding period for a period of twelve months counted from the birth of the son or daughter. The right to food for the pregnant woman is independent of the right to food for the unborn son or daughter. This means that the pregnant woman can demand support from the father or alleged father of the child, even if paternity has not been recognized. The pregnant woman has the right to request food to cover her needs during the gestation period and after giving birth, since in this way the legal norm seeks to protect the right to life and integrity of the unborn, through well-being. of the pregnant mother The person obliged to provide this alimony for the pregnant woman is the presumed father of the unborn child, since the Code of Children and Adolescents (2003) in its Art. 150 orders that all the rules of the right to alimony for children must apply to favor of the surrogate mother, insofar as they are compatible. However, according to this mandate of the Code of Children and Adolescents (2003), if the obligor of the pregnant mother proposes a reduction in child support for her children, the provision of food to the pregnant woman is not considered as an family burden, which affects the rights of the obligor Keywords: food, pregnant woman, family burden.